INVESTIGATING THE ENGLISH TEACHING AT EXCELLENT CLASS AT MTsN 2 KOTA KEDIRI - Jihan Ilmiatul Chasanah; Fathor Rasyid; Nurul Aini (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
The aim of this study is to know the implementation of teaching English at MTsN 2 Kota Kediri. The researcher used the descriptive qualitative method. The subjects of the research consisted of two English teachers who teach in 7 and 8 grades of excellent classes at MTsN 2 Kota Kediri. The data collection techniques used triangulation consisting of observation by using the observation sheets and field notes during the observation. The finding shows that there are several strategies that the teachers used at MTsN 2 Kota Kediri in teaching English including listening strategy, speaking strategy, reading strategy, and writing strategy. There are several media that the teachers used at MTsN 2 Kota Kediri, including visual media, audio media, audiovisual media, and multimedia.